High-speed video image analysis of ski jumping flight posture - Murakami, M.; Iwase, M.; Seo, K.; Ohgi, Y.; Koyanagi, R. (Sports Engineering, 2014)
Ski jumping flight posture was analyzed for achieving large flight distance on the basis of high-speed video images of the initial 40 m part of 120-m ski jumping flight. The time variations of the forward leaning angle and the ski angle of attack were measured from the video images, and the aerodynamic forces were calculated from the kinematic data derived from the images. Some correlations were investigated between the initial-speed corrected flight distance and such parameters as the angles of jumper, the initial transition time and the aerodynamic force coefficients. The result indicated that small body angle of attack was a key for large flight distance in the initial phase of flight because of small drag force, and that the most distinctive fault of beginners was too large body angle of attack and ski angle of attack leading to aerodynamic stall. Too small drag force does not give an optimal condition for large flight distance because the lift force is also too small. The ratio of the lift to the drag was larger than 0.95 for advanced jumpers.